Perception and practices pertaining to prevention and control of dengue fever among rural population in Mysore district - Shabadi, Nayanabai; G. S., Vidya (International Journal Of Community Medicine And Public Health, 2017)
Background: Dengue is the most prevalent arboviral disease in human beings, with 3.6 billion people living in areas with risk of disease transmission. Many dengue prevalence studies have been conducted in urban areas but it is important to remember the often-forgotten rural population who are also affected. The objective of the study was to assess the perceptions and practices related to dengue among residents of rural community. Methods: A community based cross sectional study was conducted for a period of two months, at Suttur village of Mysore district. Total of 200 individuals were interviewed by doing house to house survey to obtain details of socio-demographic characteristics, perceptions regarding dengue and practices of preventive measures for mosquito breeding and man mosquito contact were obtained using a pre tested questionnaire. Results: In the present study 42 (21%) members had ever heard of the disease called dengue and 18 (42.85%) of them knew that dengue fever spreads by mosquito bite and 12 (28.57%) people said it spreads by drinking dirty water, none of them knew which species of mosquitoes spread dengue fever. Many of them perceive that mosquito spreading Dengue breads in dirty water and garbage. Majority of the people used bed nets, mosquito coil and fans as methods of personal protection and 97% they followed weekly cleaning of water containers to eliminate mosquito breeding. Conclusions: the study shows, the knowledge regarding cause, modes of spread of dengue and vector characteristics were poor but the practices towards mosquito control and eliminating the breeding places of mosquito were adequate.